The Fear of Making Mistakes and Its Relationship with the Low Production of Speaking Skill - Saltos Pazmiño, Joseph Musthafá (2026)
The relationship between fear of making mistakes and low oral production in the first semester of the Pedagogía de los Idiomas Nacionales y Extranjeros program at Universidad Nacional de Chimborazo during the 2025-2S academic term was analyzed. The study focused on the emotional, linguistic, and classroom factors linked to students’ participation in English-speaking activities. A quantitative and descriptive design was applied. Information was collected from the First Semester through a structured survey containing closed questions, as well as a structured observational guide applied in classes, class discussions, and oral presentations. Survey data were analyzed with descriptive statistics, and recurrent behaviors associated with fear of making mistakes in observation records were identified. The results were triangulated between the two sources. It was found that the fear of making mistakes is prevalent and significantly limits oral production. Limited vocabulary, uncertain pronunciation, grammatical accuracy, and fear of negative evaluation were the main causes. Decreased fluency, short pronunciations, frequent use of the first language, visible signs of nervousness, and strong anxiety during oral evaluations were the consequences expressed. Findings showed that low oral production was not only a matter of insufficient linguistic knowledge, but also of persistent affective barriers that restricted students’ willingness and ability to speak English.